Anaemia and cognitive function among Chinese elderly in Old Folks Homes - Suzana Shahar; Lee X.K; Siti Balkis Budin; Mokhtar Abu Bakar; Nor Aini Umar; Junara Mohd Alim (penerbit ukm, 2005)
The relationship between anaemia and cognitive function was evaluated among 35 Chinese elderly (24 men and 11 women) aged 60 to 85 years (mean age 70.1 ± 6.7 years) from five old folks homes in Klang Valley. They were interviewed to obtain information on social and health status, habitual dietary intake and cognitive function. Hodkinson’s Abbreviated Mental Test was used to measure the cognitive function. Haematological indices which included Full Blood Count (FBC), serum iron, serum ferritin, Total Iron Binding Capacity (TIBC), serum folate and serum cobalamine (vitamin B12) weremeasured using an automated analyzer. Anthropometric measurements and clinical signs of anaemia were also examined. The findings indicated that the prevalence of anaemia as assessed using haemoglobin alone was 22.9%, while iron deficiency anaemia based on low serum iron, microcytic and hypochromic criterion was detected among 5.7% of the sample. Subclinical folate and vitamin B12 deficiencies were diagnosed among 34.3% and 8.6% of the subjects. However, there was no occurrence of megaloblastic anaemia. There was a positive correlation between cognitive score with mid upper arm circumference (MUAC) (r=0.547, p<0.01) and body mass index (BMI) (r=0.501, p < 0.01). All subjects with low haemoglobin and serum iron and approximately three quarter of subjects with folate and vitamin B12 deficiencies were classified as having cognitive impairment. In conclusion, subclinical malnutrition and anaemia may play a role in the deterioration of cognitive function in the elderly